PROGRAM SYSTEM FOR EXPERT KNOWLEDGE INPUT - Valery P. Dimitrov (Вестник Донского государственного технического университета, 2018)
Functionability and structure of the expert system input unit for engineering and technological service of the complex machinery are considered. Program system interface is given.